2007
DOI: 10.1243/14680874jer00907
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of semi-volatiles in used natural gas engine oil using thermogravimetric analysis

Abstract: Semi-volatile in internal combustion engine lubricating oil may be responsible for limiting service life and can lead to in-cylinder deposit formation. In order to measure semivolatile content, a new thermogravimetric analysis (TGA) procedure has been adapted from existing soot procedures to determine the levels of semi-volatile compounds in progressively aged lubricating oil samples from a natural gas engine dynamometer test cell run. The per cent weight remaining at 550 °C, while heated at a constant rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As such, the samples were oxidised at 550 °C after preheating in a nitrogen environment 500 °C. Such protocol is in line with works of Mullins and Truhan [36] as well as Bredin et al [34], reducing the maximum temperature for the initial stage to avoid oxidation due to oxygen traces. Aside from compositional details, information on soot concentration is important for automotive applications as the amount of soot in the lubricating oil is linked to the extent of wear [22,25,37].…”
Section: Introductionsupporting
confidence: 80%
“…As such, the samples were oxidised at 550 °C after preheating in a nitrogen environment 500 °C. Such protocol is in line with works of Mullins and Truhan [36] as well as Bredin et al [34], reducing the maximum temperature for the initial stage to avoid oxidation due to oxygen traces. Aside from compositional details, information on soot concentration is important for automotive applications as the amount of soot in the lubricating oil is linked to the extent of wear [22,25,37].…”
Section: Introductionsupporting
confidence: 80%
“…However, there was no further mass loss found beyond 410°C in air. Although the boiling point of lubricant oils differs depending on the operational conditions of the oil and its properties, other studies have observed evaporation temperatures of commonly used diesel engine oil in the same temperature range [5].…”
Section: Towards An Improved Tga Oil Analysis Methodsmentioning
confidence: 99%
“…Pyrolysis of soots [12] from different origins -including engine produced soot -showed a conversion of soot into several volatile poly aromatic hydrocarbons (PAH) under similar conditions to those at which oil analysis is conducted. In recently published findings [5,13] reduction in sample mass could also be observed during TGA of engine oil under an inert atmosphere at temperatures far beyond the oil evaporation point, possibly leading to distorted results when determining soot content.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations